Biometrics of exuviae of Cordulegaster boltonii algirica Morton, 1916 (Odonata: Cordulegastridae). Issue 4 (2nd October 2018) - El Haissoufi, Mohamed; Bennas, Nard; Hernández, María Ángeles; Casanueva, Patricia; Campos, Francisco
Abstract: This study provides the first biometrics analysis of exuviae from Moroccan populations of the Ibero-Maghrebian endemic dragonfly Cordulegaster boltonii algirica Morton, 1916 collected in the Rif Mountains. Among the biometric variables that were measured, tibia length was highly correlated with the exuviae body length (BL), and can, therefore, be used to calculate the BL of partially broken exuviae. The head width exhibited the smallest coefficient of variation for both males and females and, therefore, is a valuable measurement that can be used for biometric comparison of different populations. The data presented herein will be used for future comparison with other North African and European populations of C. boltonii algirica .